Elite selection in an autocracy: The career costs of political ties - Leonie Bielefeld; Cathrin Mohr (University of Bonn and University of Cologne, Reinhard Selten Institute (RSI), 2023)
We study the selection of the political elite in an autocratic state. Using detailed CV data on potential politicians in the German Democratic Republic, we track and quantify the position of individuals in the state hierarchy over time and exploit exogenous connections between individuals that were formed through imprisonment during the Nazi Era. We find asymmetric effects of being connected to the political elite: While being linked to the state's centre of power harms high-profile careers, they have positive effects on low-profile careers. An extensive analysis of potential mechanisms shows that the negative effect of being linked to the party leadership on individuals' probability to be part of the ruling elite is in line with anti-factionalism, whereas the positive effect on low-profile careers is in line with patronage.
Keywords: D72; P16; P26; 330; Political Economy; autocracy; political elite; selection mechanisms